Mindfulness meditation moderates the relationship between five prohibitions of Buddhism and subjective wellbeing: A survey of Vietnamese adult - Phong, Nguyen Van (Linguistics and Culture Review, 2022)
Vietnam is a country of religious diversity, in which Buddhism has the most significant participation. In addition to practicing the Five Precepts, many Vietnamese people have registered for active mindfulness meditation classes recently. This fact has received significant attention from scientists to add to the evidence of previous studies. Enrich the research literature, so the study explores the role of mindfulness meditation practice as a moderator of the relationship between five precepts practice and subjective perception well-being of Vietnamese adults. This study was conducted through a cross-sectional survey using an intentional sampling technique (n=200). Multivariable linear regression analysis and moderator regression were applied to prove the hypotheses. Research results show a positive and meaningful relationship between practicing mindfulness meditation, practicing the five precepts and feeling subjective happiness. In particular, mindfulness meditation acts as a moderating variable between the practice of the five sexes and the subjective feeling of happiness.